Why and how the brain weights contributions from a mixture of experts. (April 2021) - O'Doherty, John P.; Lee, Sang Wan; Tadayonnejad, Reza; Cockburn, Jeff; Iigaya, Kyo; Charpentier, Caroline J.
Highlights: The brain can be thought of as a "Mixture of Experts" in which different expert systems propose strategies for action. This is accomplished by keeping track of the reliability of the predictions within each system. Control over behavior is allocated in a manner that depends on the relative reliability of those predictions. The "Mixture of Experts" manager is domain general, exerting control over diverse experts to yield sophisticated behavior. Abstract: It has long been suggested that human behavior reflects the contributions of multiple systems that cooperate or compete for behavioral control. Here we propose that the brain acts as a "Mixture of Experts" in which different expert systems propose strategies for action. It will be argued that the brain determines which experts should control behavior at any one moment in time by keeping track of the reliability of the predictions within each system, and by allocating control over behavior in a manner that depends on the relative reliabilities across experts. fMRI and neurostimulation studies suggest a specific contribution of the anterior prefrontal cortex in this process. Further, such a mechanism also takes into consideration the complexity of the expert, favoring simpler over more cognitively complex experts. Results from the study of different expert systems in both experiential and social learning domains hint at the possibility that this reliability-based control mechanism is domain general, exerting control over many different expert systems simultaneously in order to produce sophisticated behavior.